Direitos humanos na Argentina (1976-1983) e no Brasil (1964-1985): Um estudo comparado sobre as rupturas constitucionais e as leis de anistia - Santos, Bruno Bernardo Nascimento dos (2019)
The present work addresses the comparative study between the last dictatorships in Argentina (1976-1983) and in Brazil (1964-1985). Both countries are founding members of the United Nations (1945) and original members of the Organization of American States (1948). During the period of oppression and political persecution of the authoritarian system of government in these countries, occurred constitutional ruptures and serious Human Rights violations perpetrated by agents of the State. The events that took place during this period were classified as crimes against humanity by the Inter-American System for the Protection of Human Rights and therefore are imprescriptible crimes. The authoritarian governments institutionalized an entire apparatus to guarantee the legality and legitimacy of the dictatorial system with deeper stages of repression. The adopted methodology was historicaldocumentary and bibliographic. The objective of the investigation is to analyze the violations of civil rights, the liberty and the individual and collective integrity of citizens during the last dictatorial regimes in these countries and how the Inter-American Court of Human Rights interprets the imprescriptibility of crimes against humanity and the question of amnesty laws